Density and temperature diagnostics of solar emission lines from Ne VI and Mg VI - Raju P.K.; Gupta A.K. (My University, 2025)
Line intensity ratios of Ne VI lines with respect to a resonance line of Mg VI have been considered for electron density and temperature determinations within the chromosphere-corona transition region. The electron pressure within the transition region has been assumed to be constant. In addition, these ratios would enable us to estimate the relative element abundances of neon to magnesium. An attempt has been made to explain the extreme ultraviolet intensities of Ne VI and Mg VI lines as observed by ATM ultraviolet spectrometer. The observed intensities correspond to the average quiet-Sun conditions near solar minimum. Theoretical intensities for Ne VI and Mg VI lines have been computed using a model solar atmosphere. Theoretical intensities obtained by using the values 3.98 × 10-5 and 3.16 × 10-5 for element abundance of Ne and Mg, respectively, seem to agree well with the expected intensities. The agreement between some of the expected and computed intensities suggests the need for future observations at higher spectral resolutions to resolve difficulties arising out of blending due to two or more lines. © 1993 Kluwer Academic Publishers.